(x-8)(x-8)=49

Simple and best practice solution for (x-8)(x-8)=49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-8)(x-8)=49 equation:


Simplifying
(x + -8)(x + -8) = 49

Reorder the terms:
(-8 + x)(x + -8) = 49

Reorder the terms:
(-8 + x)(-8 + x) = 49

Multiply (-8 + x) * (-8 + x)
(-8(-8 + x) + x(-8 + x)) = 49
((-8 * -8 + x * -8) + x(-8 + x)) = 49
((64 + -8x) + x(-8 + x)) = 49
(64 + -8x + (-8 * x + x * x)) = 49
(64 + -8x + (-8x + x2)) = 49

Combine like terms: -8x + -8x = -16x
(64 + -16x + x2) = 49

Solving
64 + -16x + x2 = 49

Solving for variable 'x'.

Reorder the terms:
64 + -49 + -16x + x2 = 49 + -49

Combine like terms: 64 + -49 = 15
15 + -16x + x2 = 49 + -49

Combine like terms: 49 + -49 = 0
15 + -16x + x2 = 0

Factor a trinomial.
(1 + -1x)(15 + -1x) = 0

Subproblem 1

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Subproblem 2

Set the factor '(15 + -1x)' equal to zero and attempt to solve: Simplifying 15 + -1x = 0 Solving 15 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -1x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -1x = 0 + -15 -1x = 0 + -15 Combine like terms: 0 + -15 = -15 -1x = -15 Divide each side by '-1'. x = 15 Simplifying x = 15

Solution

x = {1, 15}

See similar equations:

| 8*(x-2)+16=6*(x-2) | | x^2+12=72 | | x-(-9.9)=2.1 | | 6-5(3x-3)=-39 | | x+7.1=3.9 | | 9x+56=16x+10 | | 8*(x-2)+16=24/8 | | 3x-8=26 | | 8*(x-2)+16=24 | | 3(y+3)-8y=24 | | 3(n-9)-(1-n)= | | x^3-x^2-9x+9=0 | | x-3.1=4.1 | | 275=18-x | | 4b^2+5b^2-2b^2-5b^2= | | 3x-6x=5 | | x-9.9=7.9 | | 4x+50+x+43=180 | | 4x+x+43=180 | | x-5.1=3.1 | | 7*(x+3)+10=21 | | 6x+6x=16-4x | | 6x+6x=16-4 | | 2(w+7)=-2w+42 | | x+3.1=9.1 | | 101-3x=3x+11 | | 3x-17=-27 | | 7*(x+2)=21 | | x+4.9=6.1 | | 2x+8x=68-4x | | 67-5X=13X+17 | | t^2=12 |

Equations solver categories